Nanocrystalline β-NiS: a redox-mediated electrode in aqueous electrolyte for pseudocapacitor/supercapacitor applications - Kushwaha, Vishal; Gupta, Asha; Choudhary, Ram Bilash; Mandal, K. D; Mondal, Rakesh; Singh, Preetam (Physical chemistry chemical physics : PCCP, 2022)
Currently, enhancing the performance of electrochemical supercapacitors is the subject of intense research to fulfill the ever-increasing demand for grid-scale energy storage and delivery solution, thereby utilizing the full potential of renewable energy resources and decreasing our dependence on fossil fuels. Metal sulfides, such as cobalt sulfide (CoS), nickel sulfide (NiS), molybdenum sulfide (MoS), copper sulfide (CuS), and others, have recently emerged as a promising class of active electrode materials, alongside other supercapacitor electrode materials, due to their relatively high specific capacitance values and exceptional reversible redox reaction activities. The synthesis, characterizations, and electrochemical performances of single-phase nanocrystalline β-NiS are presented here and the electrode based on this material shows a specific capacitance of 1578 F g −1 at 1 A g −1 from the galvanostatic discharge profile, whereas a capacitance of 1611 F g −1 at 1 mV s −1 was obtained through the CV curve in 2 M KOH aqueous electrolyte. Additionally, the electrode also performs well in neutral 0.5 M Na 2 SO 4 electrolytes resulting in specific capacitance equivalent to 403 F g −1 at 1 mV s −1 scan rate. The high charge storage capacity of the material is due to the superior intercalative (inner) charge storage coupled with the surface (outer) charges stored by the β-NiS electrode and was found to be 72% and 28%, respectively, in aqueous 2 M KOH electrolyte. This intercalative charge storage mechanism is also responsible for its excellent cycling stability. Additionally, we assembled aqueous asymmetric supercapacitors (ASCs) with activated carbon (AC) as the negative electrode and the β-NiS electrode as the positive electrode. The combination of the β-NiS electrode and AC with excellent cycling stability resulted in the highest specific energy equivalent to ∼163 W h kg −1 and a specific power of ∼507 W kg −1 at 1 A g −1 current rate. The high charge storage capacity (1578 F g −1 at 1 A g −1 ) of β-NiS electrode is due to the superior intercalative (inner) charge storage coupled with the surface (outer) charges stored by the single phase β-NiS electrode.